Transforming Elementary School Libraries as Centers for Elementary Education Literacy - Alfiyatul Khusna; Fitri Azizah (Penerbit Presisi Pustaka, 2026)
The transformation of Madrasah Ibtidaiyah libraries is an important step in strengthening the culture of literacy at the elementary educatio level. Libraries are no longer understood merely as spaces for storing books, but as learning resource centers that support comprehensive learning processes. This study aims to describe the forms and impacts of library transformation at the elementary education level on the development of students’ literacy skills. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that library transformation is carried out through the strengthening of facilities and collections, service innovations, and the integration of literacy programs into learning activities. Efforts to reorganize library spaces and expand reading materials have created a more conducive literacy environment. Service innovations, such as reading programs, storytelling activities, and the use of simple digital catalogs, contribute to increasing students’ reading interest. The integration of libraries with learning activities encourages their utilization as reference sources and spaces for academic exploration. Despite facing challenges such as limited budgets, inadequate digital facilities, and a lack of training for librarians, library transformation has proven to have a positive impact on strengthening basic literacy. This study emphasizes the need for continuous support from schools, the government, and the community to optimize the role of libraries as literacy centers in Madrasah Ibtidaiyah.